The relationship between eye movements and subsequent recognition: Evidence from individual differences and amnesia. (December 2016) - Olsen, Rosanna K.; Sebanayagam, Vinoja; Lee, Yunjo; Moscovitch, Morris; Grady, Cheryl L.; Rosenbaum, R. Shayna; Ryan, Jennifer D.
Abstract: There is consistent agreement regarding the positive relationship between cumulative eye movement sampling and subsequent recognition, but the role of the hippocampus in this sampling behavior is currently unknown. It is also unclear whether the eye movement repetition effect, i.e., fewer fixations to repeated, compared to novel, stimuli, depends on explicit recognition and/or an intact hippocampal system. We investigated the relationship between cumulative sampling, the eye movement repetition effect, subsequent memory, and the hippocampal system. Eye movements were monitored in a developmental amnesic case (H.C.), whose hippocampal system is compromised, and in a group of typically developing participants while they studied single faces across multiple blocks. The faces were studied from the same viewpoint or different viewpoints and were subsequently tested with the same or different viewpoint. Our previous work suggested that hippocampal representations support explicit recognition for information that changes viewpoint across repetitions (Olsen et al., 2015). Here, examination of eye movements during encoding indicated that greater cumulative sampling was associated with better memory among controls. Increased sampling, however, was not associated with better explicit memory in H.C., suggesting that increased sampling only improves memory when the hippocampal system is intact. The magnitude of the repetition effect was not correlated with cumulative sampling, nor was it related reliably to subsequent recognition. These findings indicate that eye movements collect information that can be used to strengthen memory representations that are later available for conscious remembering, whereas eye movement repetition effects reflect a processing change due to experience that does not necessarily reflect a memory representation that is available for conscious appraisal. Lastly, H.C. demonstrated a repetition effect for fixed viewpoint faces but not for variable viewpoint faces, which suggests that repetition effects are differentially supported by neocortical and hippocampal systems, depending upon the representational nature of the underlying memory trace.